Rationale and design of the European Polyp Surveillance (EPoS) trials - Jover, Rodrigo; Bretthauer, Michael; Dekker, Evelien; Holme, Øyvind; Kaminski, Michal F.; Løberg, Magnus; Zauber, Ann G.; Hernán, Miguel A.; Lansdorp-Vogelaar, Iris; Sunde, Annike; McFadden, Eleanor; Castells, Antoni; Regula, Jaroslaw; Quintero, Enrique; Pellisé, Maria; Senore, Carlo; Kalager, Mette; Dinis-Ribeiro, Mario; Emilsson, Louise; Ransohoff, David F.; Hoff, Geir; Adami, Hans-Olov (Endoscopy, 2016)
Background: Current guidelines recommend surveillance colonoscopies after polyp removal depending on the number and characteristics of polyps, but there is a lack of evidence supporting the recommendations. This report outlines the rationale and design of two randomized trials and one observational study investigating evidence-based surveillance strategies following polyp removal.Study design and endpoints: The EPoS studies started to recruit patients in April 2015. EPoS study I randomizes 13 746 patients with low-risk adenomas (1 – 2 tubular adenomas size < 10 mm, low-grade dysplasia) to surveillance after 5 and 10 years, or 10 years only. EPoS study II randomizes 13 704 patients with high-risk adenomas (3 – 10 adenomas or adenoma ≥ 10 mm in diameter, or adenoma with high-grade dysplasia, or > 25 % villous features) to surveillance after 3, 5, and 10 years, or 5 and 10 years only. EPoS study III offers surveillance after 5 and 10 years to patients with serrated polyps ≥ 10 mm in diameter at any location, or serrated polyps ≥ 5 mm in diameter proximal to the splenic flexure. All polyps are removed before patients enter the trials. The primary end point is colorectal cancer incidence after 10 years. We assume a colorectal cancer risk of 1 % for patients in EPoS I, and 2 % for patients in EPoS II. Using a noninferiority hypothesis with an equivalence interval of 0.5 % for EPoS I and 0.7 % for EPoS II, the trials are 90 % powered to uncover differences larger than the equivalence intervals. For EPoS III, no power analyses have been performed.Conclusions: The present trials aim to develop evidence-based strategies for polyp surveillance, thereby maximizing effectiveness and minimizing resources.Trial registration: ClinicalTrials.gov (NCT02319928).